Defense strategy for the post-Saddam era - O'Hanlon, Michael E. (Brookings Institution Press, 2005)
"Offers pragmatic policy recommendations for strengthening the U.S. military's ability to respond to international crises, with engagement or deterrence, and protect American citizens while maintaining fiscal responsibility, by expanding ground forces yet containing spending, modernizing weaponry, implementing privatization and reform, and encouraging burden sharing with allies"--Provided by publisher.